Ethos, Pathos, and Logos: Decoding Rhetorical Strategies in Sunyako Mulya - Subedi, Yubaraj (Journal of Janta Multiple Campus, 2025)
This paper explores rhetorical strategies in Sunyako Mulya. Drawing on classical theory of persuasion propounded by Aristotle and other prominent modern rhetorical theorists and scholars, the study examines how the text constructs credibility, evokes emotion, and employs logical reasoning to engage readers. All three persuasive strategies ethos, pathos and logos are used as tools. The research method in this article includes interpretive textual analysis. Free translation has been used while taking the citation from the book. Through qualitative textual analysis, the findings reveal that the text effectively integrates these rhetorical appeals to engage readers emotionally, establish credibility and support arguments with logical reasoning. These strategies have made the book a profoundly emotional, logical and credible one. By bridging rhetorical theory and Nepali literature, this study contributes to a broader understanding of persuasion in literary texts and opens avenues for future research on rhetorical strategies in Nepali texts.